PENGARUH KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS IIA CURUP - Alfredo, Muhamad; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2024)
This thesis discusses the influence of the quality of health services on prisoner satisfaction at the Class IIA Curup prison. The formulation of the problem in the research is how the quality of health services affects prisoner satisfaction at the Class IIA Curup Prison Polyclinic. The research aims to determine the effect of health service quality on prisoner satisfaction. This research uses quantitative research methods. The types of data used are primary data and secondary data. Sampling technique using the Krijhe Morgan table, 226 prisoners who used health services at the Curup Class IIA Prison Polyclinic are the samples. The research results showed that there is an influence of health service quality variables on prisoner satisfaction in Class IIA Curup Prison with the R Square value of 23.7% and 76.3% caused by other variables not explained in the research. Keywords: Correctional Institutions; Service Quality; Prisoners